Estudio de prefactibilidad para la instalación de una planta de producción de jelly shots a base de pisco - Vigil Sánchez, Fiorella Alexandra (2020)
The study evaluates the commercial, technical, financial, economic and social viability of the installation of a jelly shots production plant of different flavors (lemon, pineapple and strawberry) based on pisco. The product is composed of gelatin dissolved in water, pure pisco and food preservative, presented in bags of 24 units of sealed shots, of 30 gr. each. With the installation of a jelly shots processing plant, an innovative product would be launched into the market, considering that the peruvian consumer has several options when they have to choose a liquor for celebrations. However, pisco has been chosen as the base drink for the product, taking into consideration that it is the official flag drink and is definetely a symbol of Peruvian identity. An annual demand of 195,747 bags of 24 jelly shots units is projected for the fifth year of the project. The target audience is made up of people between 18 and 40 years old, belonging to socioeconomic levels A and B, who live in Lima Metropolitana and are interested in the consumption of products with low alcohol content and innovators, wich are a different option in social meetings. The plant is located in the district of Lurín, department of Lima and has an area of 238 m². It has an annual capacity of 157,377 liters and the production process consists of dissolving the gelatin in hot water, mixing with the pisco and food preservative, filtering the result to avoid any suspension particles, packaging in plastic cups of 30 gr., seal with aluminum film, let it cool, pack in bags of 24 units and pack them in boxes containing 12 bags each. The total investment is S /. 557,050, where 60% is financed through a loan from the Caja Metropolitana and 40% is the share capital. The economic and financial evaluation was carried out within a period of five (05) years and the opportunity cost is 17.38%. The project generates beneficial results for shareholders, because the NPV is S/. 181,807.08, the EIRR is 27.01%, the benefit/cost ratio is 1.33 and the recovery period is 3.62 years.